Relationship between movement time and ground reaction force in the intermediate phase of baseball hitting to base running - Ohyama, K.; Maeda, A. (International Journal of Sports Science & Coaching, 2025)
Offensive play in baseball consists of batting and base running; however, the transitional phase that links these two actions, termed Situation Integration, has not been adequately studied. Furthermore, the importance of a rapid shift from batting to base running remains unclear. The purpose of this study was to identify factors that contribute to shortening Motion Time by focusing on ground reaction forces (GRF) during Situation Integration and examining their relationship with Motion Time. Twelve right-handed male collegiate baseball players (height: 170.6 ± 4.1 cm; weight: 74.2 ± 4.6 kg) were recruited. Trials were conducted for three pitch locations (Inside, Middle, Outside), and performance data were captured using an optical motion-capture system (Mac3D; Motion Analysis Corporation, Santa Rosa, CA, USA; 16 Raptor-E cameras) and a force plate (TF-90100; Tec Gihan, Uji, Japan; 2000 Hz). Pearson's correlation analysis revealed a significant negative correlation between Swing Speed for outside pitches and Motion Time (p < .05). Furthermore, when examining the relationship between time to Peak Force and Motion Time in a local coordinate system rotated so that the Y-axis pointed toward first base, it was found that achieving peak anterior GRF immediately after impact was important across all pitch locations. These results suggest that, during situation integration, rapid initiation of base running depended not on the magnitude of peak GRF but on attaining the anterior component of peak GRF earlier by reducing the time to Peak Force.